Desain dan Analisis Hasil Penggunaan Hydraulic Lift Tables pada Proses Material Handling Perakitan Mesin Konveyor di PT Roda Pasifik Mandiri - Supandi, Supandi; Purnomo, Adhy; Aditya, Muhammad Yoga Andika (Journal of Mechanical Engineering and Applied Technology, 2023)
Along with the development of technology, the development of electric bicycles in Indonesia is targeted to be able to produce as many as two million units in 2025. To meet increasing market demand shortly, PT Roda Pasifik Mandiri is increasing the production process by adding a conveyor machine as a tool to assist in the assembly process. electric bicycle products. Problems were found during the process of making the conveyor machine, namely the process of moving the conveyor frame was still carried out using the conventional method of being lifted by 6 workers. This causes a long time for the process of moving the conveyor frame before being assembled into 1 complete conveyor machine. The purpose of this research is to design and build hydraulic lift tables to reduce manpower and reduce the processing time for moving conveyor frames. The method used is the Root Cause Analysis (RCA) method which consists of defining the problem, understanding the problem, immediate action, corrective action, and confirming the solution. The tests carried out were cycle time testing before and after using hydraulic lift tables. The results of this study are that the hydraulic lift tables can reduce the processing time from 21.02 minutes to 8.9 minutes with a percentage of 56.6%.